HDAC6, modulated by miR-206, promotes endometrial cancer progression through the PTEN/AKT/mTOR pathway - Zheng, Yawen (Sci Rep, 2020)
Endometrial cancer (EC) is the sixth most common cancer in women. Since early EC has a good prognosis, identifying methods for early diagnosis is valuable. Here, we aimed to study the role of HDAC6, which has been indicated important in many kinds of cancers, in EC diagnosis and therapy. First, the expression levels of HDAC6 in EC tissues and cells were measured by qRT-PCR and Western blotting, and through bioinformatics and dual luciferase assays, HDAC6 was found to be a direct target of miR-206. Then, CCK-8, colony formation, wound healing, and Transwell assays were performed; these results indicated that HDAC6 promoted EC cell proliferation, metastasis and invasion, while miR-206 produced the opposite effects. In addition, rescue assays verified that the effect of miR-206 could be reversed by HDAC6, and global gene expression analysis confirmed the relationship between miR-206 and HDAC6. Finally, we measured the levels of PTEN, p-AKT and p-mTOR and other key molecules and speculated that miR-206 might target HDAC6 to suppress EC progression via the PTEN/AKT/mTOR pathway. In conclusion, downregulation of miR-206 and upregulation of HDAC6 in EC may predict poor prognosis, and as the target gene of miR-206, HDAC achieves its carcinogenic effect through the PTEN/AKT/mTOR pathway.